Value-driven modulation of visual perception by visual and auditory reward cues: The role of performance-contingent delivery of reward - Antono, Jessica Emily; Vakhrushev, Roman; Pooresmaeili, Arezoo (Frontiers in Human Neuroscience, 2022)
Perception is modulated by reward value, an effect elicited not only by stimuli that are predictive of task-contingent delivery of reward (TC) but also by stimuli that were previously rewarded (PR). TC and PR cues may engage different mechanisms relying on goal-driven versus stimulus-driven prioritization of high value stimuli, respectively. However, these two modes of reward modulation have not been systematically compared against each other. This study employed a behavioral paradigm where participants’ visual orientation discrimination was tested in the presence of task-irrelevant visual or auditory reward cues. In the first phase (TC), correct performance led to a high or low monetary reward dependent on the identity of visual or auditory cues. In the subsequent phase (PR), visual or auditory cues were not followed by reward delivery anymore. We hypothesized that TC cues have a stronger modulatory effect on visual discrimination and pupil responses compared to PR cues. We found an overall larger task-evoked pupil dilation in TC compared to PR phase. Whereas TC and PR cues both increased the accuracy of visual discrimination, value-driven acceleration of reaction times and pupillary responses only occurred for TC cues. The modulation of pupil size by high reward TC cues was strongly correlated with the modulation of a combined measure of speed and accuracy. These results indicate that although value-driven modulation of perception can occur even when reward delivery is halted, stronger goal-driven control elicited by task-contingent reward cues additionally results in a more efficient balance between accuracy and speed of perceptual choices.